Determination of the northeast section of the Nanyuan–Tongxian fault in Beijing and research on its Quaternary activity - NIU Wenzhi; HE Fubing; LIU Zhenhua; CUI Yubin; BAI Lingyan; WANG Anguo; ZHANG Yueze; CAO Mengmeng; ZHOU Jieming (Dizhi lixue xuebao, 2023)
The Nanyuan–Tongxian fault is the boundary fault between the Beijing depression and the Daxing uplift, also the primary seismic-controlling fault of the Beijing M \begin{document}$ 6{\dfrac{1}{2}}$\end{document} earthquake in 1665. Its activity is of great significance to land planning and geological disaster prediction in Beijing. Using high-precision gravity, longitudinal-wave and shear-wave seismic comprehensive exploration profiles, and composite borehole geological profiles, this study investigated the geometric characteristics and activity of the northeastern section of the Nanyuan–Tongxian fault. The results show that after passing through Pingjiatuan Village in Tongzhou District, the fault turns to a nearly east-west direction, trending north with a dip angle of 56° to 75°. The new activity in the northeastern section exhibits characteristics of a normal fault, with an estimated buried depth of about 21.6 m, indicating it as a late Pleistocene active fault. The findings demonstrate that the activity age of the northeast section of the Nanyuan–Tongxian fault differs from that of the middle and southwestern sections, providing crucial geological foundations for the spatial planning and disaster reduction systems in the Beijing region.